(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article scientifically analyzes the mastery of creating a female image in the novel “Stepmother” by Ahmad Lutfi Qozonchi, one of the prominent representatives of modern Turkish literature. The study substantiates that the writer depicts the female image free from traditional stereotypes, in a harmony of complex psychological and social layers. In the work, the female image is interpreted not only as a person within the family circle, but also as a symbol of moral support, patience, endurance, and devotion in society. The article reveals the role of artistic psychologism, internal monologue, conflict, and character creation methods in раскрытие the female image.